2023
DOI: 10.1002/app.53746
|View full text |Cite
|
Sign up to set email alerts
|

Alkyds with artistic applications based on drying oils, multifunctional polyalcohols and different polybasic acids

Abstract: Today's requirements in the art field have challenged researchers to create artistic paintings with attractive appearance and long‐term color stability. Alkyd‐based art mediums have become an important group in the art field, because of their similar characteristics to traditional oils and exceptional drying properties. In this work, high solid alkyd‐based art mediums have been synthesized by the monoglyceride and acidolysis processes. Multifunctional polyols and high unsaturated fatty acid sources were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…This inherent characteristic gives alkyd resins the advantage of being single component coatings and, due to their oily content, they can better tolerate the presence of rust on the surface. In addition to being easy to apply, these vegetable oil-based coatings are cheap and have been successfully used in a variety of applications, including industrial, decorative, architectural or artistic coatings [3][4][5][6]. In recent years, they are being explored for self-healing applications to ensure the long-term durability of protective coatings [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This inherent characteristic gives alkyd resins the advantage of being single component coatings and, due to their oily content, they can better tolerate the presence of rust on the surface. In addition to being easy to apply, these vegetable oil-based coatings are cheap and have been successfully used in a variety of applications, including industrial, decorative, architectural or artistic coatings [3][4][5][6]. In recent years, they are being explored for self-healing applications to ensure the long-term durability of protective coatings [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has shown that sacha inchi oil is a new and effective feedstock for alkyd resins synthesis in the surface coating industry, either as pure oil [17,[24][25][26], through its fatty acids [16] or as part of an oil mixture [27,28]. Its effectiveness has also been proven as a raw material for the creation of artistic products [6]. Currently, sacha inchi seeds are used for oils, cakes and protein meals, and are highly used in the cosmetic, food and medicine industry [28].…”
Section: Introductionmentioning
confidence: 99%